AVANZÂDE MEHMET SÜLEYMAN'IN SABAH GAZETESİNDEKİ “MUSAHABE-İ NİSÂİYE” YAZILARINDA KADIN ALGISI - KANTER, Beyhan; ÇONOĞLU, Salim (Hacettepe University, 2025)
Avanzâde Mehmet Süleyman has taken an active position in the Ottoman women's movement, with her rich oeuvre, especially for women, in Turkish literature and cultural history. He undertakes a guiding mission in her writings in which he expresses her views encompassing the traditional vision of femininity. He, who stood out with her conservative identity within a male-dominated system and emphasized the traditional vision of femininity at every opportunity, published articles for women under the title of “Musahabe-i Nisâiye” in the Sabah newspaper in 1899. With these articles, he guided Muslim Ottoman women on the one hand and provided information about the daily life practices of women in different geographies of the world. On the other hand, he compared Muslim and European women in terms of cultural, customary, and religious elements and gave advice to Muslim women. Avanzâde Mehmet Süleyman's advice on skin care, beauty, and health for women also took an important place in his articles in Sabah newspaper. The author covered some of his articles in the Sabah newspaper from different publications in the following years. In this article, the articles of Avanzâde Mehmet Süleyman, one of the writers of the Constitutional Era, in his column “Musahabe-i Nisâiye” in Sabah newspaper, will be examined from a comparative perspective in the context of the socio-cultural characteristics of the period. By comparing them with publications on women in the Ottoman press, a perspective on the understanding of women in the period is presented. © (2025), (Hacettepe University). All rights reserved.
Keywords: Avanzâde Mehmet Süleyman; Europe; Islam; Sabah; Women